2019
DOI: 10.18805/ijar.b-1062
|View full text |Cite
|
Sign up to set email alerts
|

Caecal microbiome and metabolites associated with different growth performances of broilers

Abstract: We investigated changes in the caecal microbial composition and metabolic compounds of broiler chickens weighing approximately 0.8–1.5 kg. Arbor Acres (AA) broilers (n =186) were divided into four groups (A–D) according to body weight on day 35. The results showed that there were significant differences in the average daily feed intake (ADFI), average daily gain (ADG), and feed-to-gain ratio (F:G) of chickens (P less than 0.05). The abundance of 11 genera were found to be significantly different in the four gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The gut microbiota is closely related to poultry productivity ( Diaz Carrasco et al, 2019 ). Chen et al (2019) showed that the cecal microbiome and metabolites contribute more efficiently to a higher growth performance in chickens. Yan et al (2017) showed that Lactobacillus and Akkermansia had significantly higher abundance in the cecal contents of hens with better feed efficiency and enriched functions related to carbohydrate and amino acid metabolism, suggesting that Lactobacillus can improve the feed efficiency of hosts.…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiota is closely related to poultry productivity ( Diaz Carrasco et al, 2019 ). Chen et al (2019) showed that the cecal microbiome and metabolites contribute more efficiently to a higher growth performance in chickens. Yan et al (2017) showed that Lactobacillus and Akkermansia had significantly higher abundance in the cecal contents of hens with better feed efficiency and enriched functions related to carbohydrate and amino acid metabolism, suggesting that Lactobacillus can improve the feed efficiency of hosts.…”
Section: Introductionmentioning
confidence: 99%